Quality Control Software for a Gamma Spectrometer - Kivelä, Sari (My University, 2020)
Gamma radiation is electromagnetic radiation from the radioactive decay of atomic nuclei. Gamma spectrometry is a science that identifes and quantifes gamma-ray emitting radionuclides in a sample by analyzing the energy spectrum produced by plotting a histogram of the number of detected signals against the energies of the detected gamma photons. Applications of gamma spectrometry include nuclear medicine, life science research, and environmental monitoring. In these applications, the reliability of the results is very important. Quality control (QC) of the spectrometer instrument ensures the reliability of results by detecting any deviations in the performance of the instrument and defning the corrective actions. Central part of the quality control of gamma spectrometers are regular QC measurements of known radiation reference sources, and regular background radiation level measurements. In this thesis, a quality control software module was designed and implemented for a larger software that is used to operate and analyze the results of a gamma spectrometer. The main goals of the thesis were to collect the quality control features into a common place in the user interface, where the QC status of the instrument is readily visible, and to design the QC workfow in a way that guides the user in recognizing and performing the necessary QC actions.
Keywords: gamma, radiation, spectrometry, quality control